Penguatan Pendidikan Karakter Cinta Lingkungan melalui Pembelajaran dengan Memanfaatkan Media Loose Parts pada Anak Usia Dini - Hamidah, Lia Yulia; Wahidin, Didin; Handayani, Sri (Edukasi: Journal of Educational Research, 2022)
The research "strengthening environmental love character education through learning by utilizing loose parts media in early childhood", is motivated by the weak character values ​​of early childhood love for the natural environment as a place to play and lack of creativity in using Loose parts media in the environment as a source of play , due to the fact that early childhood learning (AUD) prioritizes the cognitive domain over character and creativity, gadgets become playmates rather than playing with the environment, an environment where exploration of environmental love characters changes its function. The purpose of the study in general is to obtain an overview and describe the strengthening of environmental love character education in early childhood which is directly proportional to Lickona's character theory (1991:23), specifically analyzing planning, organizing, implementing and evaluating, according to the management theory of Gorge R Terry ( Athoillah 2010:16). The research procedure uses a qualitative approach with case study methods at PAUD Alam Pelopor and PAUD Ceria Bandung Regency. The results of the study (1) Planning for strengthening the character of love for the environment is prepared for curriculum programs, objectives, processes and learning materials referring to the 2013 PAUD curriculum which was developed into the education unit level curriculum (KTSP) but the planning, infrastructure and budget have not been adjusted to the Covid-19 Pandemic period. 19.(2) Organizing the strengthening of character education for the love environment of school principals, structuring the parties involved according to their duties and responsibilities, and aligning core competencies (KI), basic competencies (KD), and STTPA with six aspects of early childhood development in learning according to characteristics, principles, methods , and the type of learning, has been implemented well. (3) Implementation of planning for organizing and implementing learning to strengthen character education for environmental love based on PROMES, RPPM, and RPPH with themes and sub-themes carried out through planting, growing, developing, and strengthening the opening, core, and closing activities, but implementing learning during the pandemic Covid-19 lacks parental support and networks, so it is not carried out properly. (4) Evaluation of strengthening character education for the love of the environment is seen from the constraints and solutions of teacher competence and the learning process, internal and external evaluations of character achievement assessments for students and assessments from peers, supervisors and the government. The purpose of the evaluation is to measure programs that have been achieved and have not been achieved, which are reflected in the next character planning. The researcher concludes that strengthening environmental love character education by utilizing loose parts media in early childhood during the Covid-19 pandemic is not all carried out well but needs improvement and adjustment.